Noise Reduction of Chaotic Signal Based on Empirical Mode Decomposition - Yang Hong; Guohui Li (Institute of Advanced Engineering and Science, 2014)
In view of the nonlinear characteristics of chaotic signal, a threshold denoising method of noisy chaotic signal based on empirical mode decomposition (EMD) is presented. Firstly, noisy chaotic signal is decomposed into several intrinsic mode function (IMF) by empirical mode decomposition. Secondly, the intrinsic mode functions of high frequency are respectively processed using threshold method. Finally, we add these IMFs with IMFs of low frequency to achieve denoising signal. The noisy Lorenz chaotic signal is chosen to perform noise reduction. Taking the noisy Lorenz chaotic signal as an example, the proposed method is used. The simulation results show that this method is an efficient method. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4015